Knowledge and attitudes of Saudi populations regarding seasonal influenza vaccination - Abdulrahman S. Alqahtani; Hosam M. Althobaity; Daifullah Al Aboud; Ahmed S. Abdel-Moneim (Elsevier, 2017)
The World Health Organization Global Vaccine Action Plan aims to accelerate the control of preventable diseases, including seasonal influenza; however, seasonal influenza vaccination reluctance persists. The current study aimed to assess the knowledge and attitudes of Saudi nationals regarding seasonal influenza vaccinations. An anonymous questionnaire was targeted to Saudi nationals for self-enrolment in this study. Data were analyzed using descriptive and chi-squared analyses. This study included 1298 Saudi nationals (745 males and 553 females) who were ≥19 years old. A total of 44.53% of the participants had been vaccinated with the seasonal influenza vaccine. In total, 26.96% of the participants were certain that there were no contradictions between the influenza vaccine and other childhood vaccines and 36.67% knew that individuals with chronic diseases should be given the seasonal influenza vaccine. By contrast, only 123 of the participants (9.48%) understood that pregnant women could be vaccinated with the influenza vaccine. Vaccinated participants in our study showed a higher level of knowledge compared to non-vaccinated participants. Most of the participants reported that the most reliable source of information was healthcare worker advice. The current study provides important information regarding misperceptions in public attitudes towards seasonal influenza vaccinations; these data can be used to plan strategies to address existing gaps in healthcare. Keywords: Seasonal influenza vaccine, Misperception, Attitudes, Awareness, Saudi Arabia